How to remove extra space before and after paragraphs in a Microsoft Word document / Naemah Abdul Wahab - Abdul Wahab, Naemah (Unit Penerbitan dan Publisiti JSKM, 2022)
You are working on a new document in Word, but it is inserting extra space between paragraphs. You have tried to highlight your document and going to the Line and Paragraph Spacing button as seen in figure below, choosing 1.0 (single spacing) option but your Word document still have those unwanted extra spaces before and after paragraphs? Is there a way to disable this? The answer is a huge YES! Follow these simple steps to remove the extra spacing between paragraphs in your Word document. a) Highlight your Word document by pressing ctrl+A. b) Go to the Home tab on the Microsoft Word ribbon. c) Find the Paragraph section. d) Click the little "more" arrow in the lower right corner of the box. e) A Paragraph window will pop-up as shown in figure below. Just focus on the Spacing options. f) Change the Before to 0 pt and After to 0 pt, then the Line Spacing drop-down menu to the spacing that you prefer (single, 1.5 lines or double). g) Lastly, click OK